(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
In the dynamic and ever-evolving hospitality industry, staying ahead of the curve is crucial for businesses to thrive. Competitive position monitoring (CPM) has emerged as an essential management tool that enables hospitality establishments to assess their strengths and weaknesses relative to their competitors, ensuring their continued success in the marketplace. The hospitality industry is pivotal in La Union’s economic growth and development. By attracting tourists from around the globe, hospitality businesses contribute significantly to the province’s revenue generation and employment opportunities. As future accountants and business professionals, the researchers recognize the importance of understanding and enhancing CPM practices within this sector. This study delves into CPM practices in the hospitality industry of La Union, a province in the Philippines renowned for its tourism attractions. The primary objective of this study is to evaluate the current CPM practices employed by hospitality businesses in La Union and identify areas for improvement. This study employs a descriptive research design, utilizing a correlational and comparative analysis approach. The study population consists of managers and employees of hospitality establishments in selected municipalities within La Union. Stratified random sampling was employed to select 145 respondents, comprising 74 managers and 71 employees. Data was gathered through a self-administered questionnaire designed to assess the level of CPM practices and their impact on business performance. The study’s findings reveal that while some hospitality businesses in La Union effectively implement CPM strategies, others lag. This lack of comprehensive CPM practices is attributed to several factors, including limited knowledge of social, economic, environmental, and sustainability (SEES) strategies. The study highlights the critical role of SEES strategies in enhancing a business’s competitive edge and ensuring its long-term sustainability. The study’s findings underscore the importance of adopting a comprehensive CPM approach that encompasses all aspects of a business, from financial performance to customer satisfaction. By effectively monitoring and evaluating their competitive position, hospitality businesses in La Union can better understand their strengths and weaknesses, enabling them to make informed decisions and strategically adapt to the ever-changing market landscape.